2022
DOI: 10.3390/cells11101648
|View full text |Cite
|
Sign up to set email alerts
|

SMER28 Attenuates PI3K/mTOR Signaling by Direct Inhibition of PI3K p110 Delta

Abstract: SMER28 (Small molecule enhancer of Rapamycin 28) is an autophagy-inducing compound functioning by a hitherto unknown mechanism. Here, we confirm its autophagy-inducing effect by assessing classical autophagy-related parameters. Interestingly, we also discovered several additional effects of SMER28, including growth retardation and reduced G1 to S phase progression. Most strikingly, SMER28 treatment led to a complete arrest of receptor tyrosine kinase signaling, and, consequently, growth factor-induced cell sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…We could readily show an increase of LC3-II in treated cells indicative of increased autophagy (Supplementary Fig. S3 ) as expected 31 and autophagic flux as recently reported 45 . More importantly, we noted a significant alteration in the appearance of the microtubule cytoskeleton.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…We could readily show an increase of LC3-II in treated cells indicative of increased autophagy (Supplementary Fig. S3 ) as expected 31 and autophagic flux as recently reported 45 . More importantly, we noted a significant alteration in the appearance of the microtubule cytoskeleton.…”
Section: Resultssupporting
confidence: 87%
“…3 d,e) or autophagy-inducing conditions (Fig. 3 f,g) at concentrations with comparable cytotoxicity 31 , 45 , 52 , 53 (Supplementary Fig. S2 c) implied two aspects: Firstly, our observations indicated that the effects of SMER28-induced MT straightening are distinct from physical MT stabilization as induced e.g.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation